Silencing of CircTRIM25/miR-138-5p/CREB1 axis promotes chondrogenesis in osteoarthritis - Chunlei He; Zhaogan Zeng; Yadong Yang; Shanshan Ye; Qiang Wu; Xunzhi Liu; Chenghong Liu; Wanhui Zeng; Sheng Liu (Autoimmunity)
Background Dysregulated circular RNAs (circRNAs) are involved in osteoarthritis (OA) progression.Objective We aimed to explore the effect of hsa_circ_0044719 (circTRIM25) on the ferroptosis of chondrocytes.Methods Chondrocytes were treated with interleukin (IL)-1β to generate cell model. Cellular behaviours were measured using cell counting kit-8, enzyme-linked immunosorbent assay, relevant kits, propidium iodide staining, and immunofluorescence assay. Quantitative real-time polymerase chain reaction was performed to examine the expression of circTRIM25, miR-138-5p, and cAMP responsive element binding protein 1 (CREB1), and their interactions were assessed using luciferase reporter analysis and RNA pull-down assay.Results CircTRIM25 was upregulated in OA tissues and IL-1β-stimulated chondrocytes. Knockdown of circTRIM25 facilitated the viability and suppressed ferroptosis and inflammation of IL-1β-induced cells. CircTRIM25 served as a sponge of miR-138-5p, which directly targets CREB1. Downregulation of miR-138-5p abrogated the effect induced by knockdown of circTRIM25. Furthermore, enforced CREB1 reversed the miR-138-5p induced effect. Moreover, knockdown of circTRIM25 attenuated cartilage injury in vivo.Conclusion Silencing of circTRIM25 inhibited ferroptosis of chondrocytes via the miR-138-5p/CREB axis and thus attenuated OA progression.